Development of hydrocracker modeling by incorporation of vapor-liquid equilibrium. (2nd May 2016) - Wang, Caijie; Cheng, Zhenmin
ABSTRACT: Vapor-liquid equilibrium by means of Peng-Robinson equation of state was incorporated into the Stangeland hydrocracker model to improve the modeling prediction precision. For this purpose, the modeling parameters such as the rate constant, product distribution, and reaction heat were all estimated by the genetic algorithm on the basis of industrial data. Investigation of the vapor-liquid equilibrium in a hydrocracker indicated that the liquid flow rate decreases significantly along with proceeding of the reaction, and at outlet of the reactor, the mass flow rate found in the vapor phase even exceeds that of the liquid phase. In a hydrocracker consisting of four beds, 77 mol% of the oil is in the vapor phase at outlet of the last stage, while it is only 30 mol% at inlet of the first stage. Analysis of simulations with and without vapor-liquid equilibrium revealed that there are significant differences in bed temperature profiles, liquid flow rates, liquid compositions, and product yields.